Radioactive ion beams in the region of $^{100}Sn and $^{78}Ni at the NSCL - Stolz, A.; Estrade, A.; Davies, A.D.; Ginter, T.N.; Hosmer, P.T.; Kwan, E.; Liddick, S.N.; Mantica, P.F.; Mertzimekis, T. J.; Montes, F.A.; Morrissey, D.J.; Morton, A.C.; et al. (Proceedings of the Sixth International Conference on Radioactive Nuclear Beams (RNB6), 2004)
The regions around the doubly magic nuclei 100Sn and 78Ni are of great interest from a nuclear structure standpoint. These nuclei also play a key role in the astrophysical rp- and r-processes, respectively. Recently, nuclei in these regions were studied at the Coupled Cyclotron Facility at the National Superconducting Cyclotron Laboratory (NSCL) at Michigan State University.